Spatially Resolved Chandra Spectroscopy of Supernova Remnant DEM L71 in the Large Magellanic Cloud. Issue 4 (10th February 2022) - Alan, N; Bilir, S
ABSTRACT: We present a detailed X-ray spectroscopic study of the supernova remnant (SNR) DEM L71 in the Large Magellanic Cloud. Based on deep ∼103 ks archival Chandra data, we perform a detailed spatially resolved spectral analysis of DEM L71. We analyse regional spectra extracted from thin-sliced regions along several different azimuthal directions of the SNR to construct radial profiles of elemental abundances for O, Ne, Mg, Si, and Fe. Our elemental abundance measurements reveal an asymmetrical spatial distribution of metal-rich ejecta gas. Especially the asymmetry in the western part of the central Fe distribution is remarkable. While the location of the contact discontinuity is generally at ∼5 pc from the geometric center of the X-ray emission of DEM L71, it is uncertain in the western part of the remnant. Fe is enhanced in the ejecta while O and Ne abundances are generally negligible. This finding confirms the Type Ia origin of DEM L71. We estimate an upper limit on the Sedov age of ∼6660 ± 770 yr and explosion energy of ∼1.74 ± 0.35 × 10 51 erg for the remnant. This explosion energy estimate is consistent with a canonical explosion of a type Ia SNR.